Effects of Dangguibuxue decoction on rat glomerular mesangial cells cultured under high glucose conditions - Ren, Xiao-Dan (BMC Complement Altern Med, 2017)
BACKGROUND: Dysfunction of glomerular mesangial cells (GMCs) plays an important role in pathogenesis of diabetic nephropathy. Here, we investigated the effects of Dangguibuxue decoction (DBD), an herbal traditional Chinese medicinal (TCM) formula composed of Astragali Radix and Angelicae Sinensis Radix, on GMC proliferation and fibrogenesis under high-glucose (HG) conditions. METHODS: Sixty male Sprague Dawley rats were divided into 5 groups and administered intragastric 0.9% saline, low concentration DBD (DBD-L, 1.75 g/kg/d), middle concentration DBD (DBD-M, 3.5 g/kg/d), high concentration DBD (DBD-H, 7.0 g/kg/d) and gliclazide (GL, 2 mg/kg/d), respectively, for 1 week, and then their sera were obtained. Rat mesangial cells (HBZY-1 cells) were treated with these sera under HG condition (30 mmol/L). RESULTS: The proliferation of GMCs under HG conditions was significantly greater than that under normal glucose condition. Low concentration DBD (DBD-L) inhibited proliferation of GMCs after 72-h incubation (P < 0.01), while high concentration DBD (DBD-H) inhibited GMCs proliferation at 24, 48 and 72 time points (P < 0.01). There was no significant difference between the inhibitory effect of DBD-H and GL sera on GMC proliferation (P > 0.05). Furthermore, all concentrations of DBD (DBD-L, DBD-M and DBD-H) significantly decreased the protein expression of α-SMA(α-smooth muscle actin) (P < 0.01), an indicator of interstitial fibrosis of GMCs. Finally, DBD-L, DBD-M, DBD-H sera obviously inhibited the increase of HYP (hydroxyproline)secretion under HG condition (P < 0.01). CONCLUSION: Our results demonstrate an inhibitory effect of DBD extract on proliferation and fibrogenesis of GMCs under HG conditions. The potential role of DBD in the treatment of diabetic neuropathy merits further investigation.